Roots of resilience: Optimizing microbe‐rootstock interactions to enhance vineyard productivity - Davide Francioli; Timo Strack; Leonie Dries; Kai Peter Voss‐Fels; Christoph‐Martin Geilfus (Plants, People, Planet)
Societal Impact Statement Grape production relies signifcantly on agrochemicals, such as fertilizers and pesticides, to sustain vine health and yield. However, excessive or improper use of these inputs leads to detrimental environmental effects, including soil degradation, water contamination, and biodiversity decline. To address this, research must explore sustainable alternatives. Enhancing the symbiotic interactions between grapevine rootstocks and beneficial soil microorganisms offers a viable pathway. By fostering these natural relationships, producers and scientists can develop environmentally sustainable viticulture practices that strengthen vine resilience without compromising productivity. This approach also supports the broader transition to regenerative, ecologically balanced agricultural systems. Summary The productivity and resilience of vineyards are influenced by complex interactions between grapevine rootstocks and the surrounding soil microbiome. Emerging research has highlighted the pivotal role of these microbe‐rootstock alliances in modulating nutrient acquisition, water‐use efficiency, and pathogen resistance. By leveraging the symbiotic potential of beneficial soil microorganisms, viticulturists can optimize vineyard management practices to enhance overall productivity, stability, and sustainability. Through the strategic selection of rootstocks with enhanced mycorrhizal associations and the targeted introduction of plant growth‐promoting rhizobacteria, growers can support the grapevine in adapting to challenging soil conditions. Aditionally, manipulating the rhizosphere microbiome, through techniques such as biofertilization and reverse microdialysis, can foster the development of robust, disease‐suppressive communities that safeguard the vines against biotic and abiotic stressors. Integrating these microbiome‐centric approaches into comprehensive vineyard management strategies, and potentially in future rootstock genetic improvement programs, holds promise for improving grape yield, quality, and the long‐term resilience of viticultural systems.